Digital-based nutrition education on nutrition knowledge and behaviors in adolescents: A systematic review - Dwiyan Fahrizki Destio; Meti Dwiriani Cesilia (BIO Web of Conferences)
Adolescence signifies a transition period from childhood to adulthood marked by various changes, including nutrition behaviors. Nutrition behaviors established during this time often persist into adulthood, influencing long-term nutritional intake and status. Fulfillment of nutritional needs is an absolute for adolescents and poor nutrition behaviors can cause nutritional problems in adolescents. Nutrition education is one way to improve the nutrition knowledge and behaviors in adolescents. The advancement of technology gives rise to new media, one of which is digital media. Digital media such as mobile apps, podcasts, social media, and video games are shown to be effective media in nutrition education for improving people's nutritional knowledge and behaviors, including in adolescents. This PRISMA review aimed to identify and synthesize all related studies to assess the effectiveness of digital-based nutrition education in adolescents’ nutrition knowledge and behaviors. All studies reported some positive outcomes on nutrition knowledge and behaviors in adolescents. In the future, a randomized controlled study a with longer duration is recommended for digital-based nutrition education.